The Relationship Between Fear-Avoidance and Neuromuscular Measures of Function in Patients With Adult Degenerative Scoliosis. Issue 23 (1st December 2018) - Haddas, Ram; Lieberman, Isador H.; Block, Andrew
Abstract : Study Design: A prospective cohort study. Objective: To examine the relationship of fear-avoidance beliefs and neuromuscular activity during gait in adult degenerative scoliosis (ADS) patients. Summary of Background Data: Among patients with chronic spine pain, fear-avoidance beliefs are predictive of poor surgical outcomes. Fear-avoi occurs when patients perceive that movement will worsen underlying physical problems. This process leads them to restrict activity, which further heightens emotional distress. Patients with ADS have previously been shown to have an altered gait pattern. Electromyography is evolving into a useful tool to further our understanding of the pathologic manifestations of ADS during gait. Methods: Fifty ADS patients completed the Tampa Scale for Kinesiophobia (TSK) questionnaire and the Fear Avoidance Beliefs Questionnaire (FABQ). Surface electromyography electrodes were bilaterally placed on trunk and lower extremity muscles. Each patient performed a series of over-ground gait trials at a self-selected comfortable speed. Pearson Product Correlation analysis was used to determine the relationship between the self-reported fear of movement measures and the neuromuscular gait analysis biomechanical data. Results: The TSK total score and the FABQ physical were correlated with muscle onset of the External Oblique ( P = 0.005), Gluteus Maximus ( P = 0.018), Multifidi ( P = 0.017), Erector Spinae ( P = 0.014), Rectus Femoris (i = 0.008), Semitendinosus ( P = 0.012), Tibilais Anterior ( P = 0.012), and Medial Gastrocnemius ( P = 0.010). Furthermore, the TSK total score, FABQ physical portion were correlated with muscle peak activity of Medial Gastrocnemius ( P = 0.007), Multifidi ( P = 0.014), and Tibilais Anterior (i = 0.050) and time to peak muscle activity of the Medial Gastrocnemius ( P = 0.006) and Semitendinosus P = 0.038. Conclusion: This study demonstrates a strong correlation between neuromuscular gait parameters and fear-avoidance of movement which may reflect ADS patient experiences during ambulation. Further, it demonstrates that there are different aspects of fear-avoidance that may influence gait parameters. This study extends previous research on the role of fear-avoidance to include patients with spinal deformity. Level of Evidence: 3